เภสัชจลนศาสตร์ประชากรของยาแวนโคมัยซินในผู้ป่วยเด็กชาวไทย - ชนิกา ชูพันธ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
This retrospective study aimed to estimate vancomycin pharmacokinetic (PK) parameters, investigate factors influencing PK parameters. A total of 348 serum vancomycin concentrations were obtained in 212 pediatric patients, aged 1 month to 18 years, who were admitted at King Chulalongkorn Memorial Hospital between 2012 to 2017. In total, this study enrolled 212 pediatric patients with 348 serum vancomycin concentrations. Median of age was 3.5 years (range 1 month – 17.9 years). Population pharmacokinetic analysis was performed using NONMEM® program with first-order conditional estimation with interaction method. Vancomycin pharmacokinetics was adequately explained by one-compartment model with first-order elimination. Mean vancomycin clearance (CL) and volume of distribution (Vd) were 0.13±0.06 L/h/kg and 0.88±0.15 L/kg, respectively. Factors influencing PK parameters were weight (kg) and estimated glomerular filtration rate (eGFR; ml/min/1.73m[superscript 2]) as shown in the following equations: CL (L/h) = 1.66*(weight/14)[superscript 0.75]*(eGFR/108.9) and Vd (L) = 12.7*(weight/14). Interindividual variability of CL was 34.8% and Vd was 39.6%. The final model was validated using bootstrap and visual predictive check (VPC). The final PK estimates were close to PK parameters from 1,000-bootstrap replicates and within 95% confidence interval of bootstrap results. VPC (1,000 replicates) showed only 6% of vancomycin concentrations distributed outside 90% confidence interval. These results suggest that the model is appropriate to describe vancomycin pharmacokinetics.